Examining Teachers’ Awareness, Practices, and Challenges in School Disaster Risk Reduction and Management Implementation in East District, Bayugan City Division - Noynay, Anima Christi P. (Randwick International of Education and Linguistics Science Journal, 2025)
This study examined the level of awareness, practices, and challenges encountered by teachers in the implementation of School Disaster Risk Reduction and Management (SDRRM) in the East District of Bayugan City Division. Employing a descriptive-correlational design, this study was participated by 113 teachers through Slovin’s formula and cluster sampling. The data gathered were analyzed employing means and Spearman’s Rank Correlation. Findings revealed that teachers exhibit high levels of awareness as well as very satisfactory levels of practice across all indicators of the Comprehensive School Safety framework which includes: Enabling Environment, Safe Learning Facilities, School Disaster Risk Management, and Disaster Risk Reduction in Education. It was found that there is a significant relationship between the teachers’ level of awareness and practices across all indicators. Nevertheless, common challenges encountered by the teachers were identified namely: inadequate funding, insufficient resources, lack of collaboration, and inadequate training. Grounded in the study’s findings, an enhanced SDRRM plan was proposed to reinforce the challenges identified. The study underlines the importance of sufficient resource allocation, continuing professional development, and widened linkages in creating a safe and resilient school community.